Comparison of Heat Transfer Performance for Condensation in Corrugated Low Finned Tube and Smooth Tube with Air. Issue 1 (June 2020) - Ren, Bin; Pu, Zhe; Tang, Xiaoying; He, Aini; Lu, Hongliang; Si, Sun
Abstract: The existence of air served as non-condensable gas makes it difficult to design effective titanium condenser in PTA plant. In this paper, the heat transfer characteristic for condensation inside corrugated low finned tube and smooth tube in presence of air was compared. The local heat transfer performance was studied by comparing bulk temperature and local heat transfer rate. The effect of non-condensable gas mass fraction on overall heat transfer performance was also analysed. The results indicated that both the bulk temperature and the local heat transfer rate decreased along the axial direction due to the reduction of steam partial pressure and temperature difference. The average heat transfer coefficient and total heat transfer rate decreased with the increase of inlet non-condensable gas mass fraction. And the corrugated low finned tube could reduce the impact of non-condensable gas by reducing the thickness of gas film and condensate film.